Review of the Fund's Policy on Multiple Currency Practices-Proposals for Reform. (Policy Papers; Policy Paper ;, 2022)
In February 2019, the Executive Board considered staff's preliminary proposals for reforming the IMF's policy on multiple currency practices (MCPs) and supported the majority of the proposals. The Board expressed strong support for re-focusing the policy on official action that segments foreign exchange markets, eliminating the concept of potentiality, and replacing the current fixed two-percent rule for identifying MCPs for spot transactions with a country-specific market-based norm and tolerance margin that would apply uniformly across the membership for both spot and non-spot transactions. The Board also supported staff's proposals regarding the other elements of the new methodology to identify MCPs, the treatment of illegal parallel markets, excluding broken cross-rates from the scope of the policy, and the linkages with the Institutional View on the Liberalization and Management of Capital Flows. The paper outlines operational considerations to address noncompliance and to ensure a smooth transition. It is proposed to enhance the current cooperative approach to addressing noncompliance by increasing transparency and accountability.